In vitro micropropagation from shoot meristems of Turkish cowpea (Vigna unguiculata L.) cv. Akkiz (Bangladesh Journal of Botany, 2008)
Multiple shoots from shoot meristems of three - five-day-old in vitro grown seedlings of Turkish cowpea (Vigna unguiculata L.) cv. Akkiz was obtained in MS supplemented with 0.50 mg/l BAP - 0, 0.10, 0.30 and 0.50 mg/l NAA. Callus induction was recorded on all cultures. Callusing was recorded on all cultures containing 0.5 mg/l BAP with and without NAA. However, increased diameter of calli was recorded on MS medium containing 0.5 mg/l BAP - 0.1, 0.3 and 0.5 mg/l NAA. The highest frequency (%) of shoot regeneration and mean number of shoots per explant was recorded on MS medium containing 0.5 mg/l BAP with out NAA. Addition of any concentration of NAA resulted in significant decrease in the frequency (%) of shoot regeneration and mean number of shoots per explant. Maximum mean number of 2.60 shoots per explant was obtained on MS without NAA. Regenerated shoots were rooted on MS containing 0.50 mg/l IBA where up to seven adventitous secondary shoots arose from the base of mother shoot were also recorded. These shoots could also be rooted easily on the same rooting medium. Rooted plants were adapted at room temprature in soil mix in pots. All plants flowered and set seeds in the growth room after three months. Key words: Cowpea, Micropropagation, Shoot meristem doi:10.3329/bjb.v37i2.1723 Bangladesh J. Bot. 37(2): 149-154, 2008 (December)